Striving for low-carbon lifestyles: An analysis of the mobility patterns of different urban household types with regard to emissions reductions in a real-world lab experiment in Berlin - Max Juri Bäuerle (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2022)
The transport sector has so far shown little success in reducing emissions. Demand-side solutions such as lifestyle and behavioural changes of individuals and private households entail extensive reduction potential that could greatly complement technological solutions in transport. Private households are therefore relevant actors through their transport demand and modal choice. Yet, challenges and opportunities for reducing emissions vary with the household living situations and individual preconditions for action. The real-world lab experiment KLIB pursued to support and motivate households that intended to reduce their carbon footprint during an one year real lab phase using a carbon tracker tool. Based on the KLIB mobility data, this study aims to enhance understanding on the extent of emissions reductions through voluntary changes in mobility behaviour. This implies to identify through which changes in modal choice and transport demand how much of emissions reductions were achieved and where obstacles and limits to voluntary efforts existed. A mixed-methods research design is adopted: transport sociologically grounded type formation groups the KLIB households along relevant household characteristics. Subsequent type-based statistical data analysis examines changes of the types' mobility patterns and associated emissions. The findings indicate that within everyday ground mobility voluntary behavioural changes like the shift to low-carbon modes can lead to considerable emissions reductions depending on the household living situation and particularly car equipment. Nevertheless, car ownership presents a strong carbon lock-in and barrier to emissions reductions. Contradictory results are provided by air travel, where emissions increase for almost all household types, offsetting or outbalancing ground mobility savings. It emerges that behavioural changes are contextspecific and constrained by counteractive effects and obstacles, especially in holiday contexts and emissions-intensive air travel.
Keywords: 300